In-vitro diffusion studies and anticancer activity of cytarabine loaded nanocochleates against MCF-7 cell lines - Niranjana Vaidhya Anantharaman; Ubaidulla Udhumansha; Grace Rathnam (International Journal of Pharmacy and Analytical Research, 2022)
Cochleates are a relatively new type of crystalline particles having a large and continuous lipid bilayer sheets rolled up in a spiral structure of less internal aqueous phases. Cytarabine is used in the treatment of the leukemia. It can bind with the cross-linking agent like calcium chloride to form the coiled structure. The Invitro diffusion studies was performed by altering the various concentrations of cross-linking agent, drug, cholesterol: the formulation has its effect by change in the release pattern and the entrapment efficiency. In this study the concentration of the crosslinking agent is related to the release pattern. The Nanocochleates is used to increase bioavailability, to achieve the maximum therapeutic efficacy, to reduce side effects and adverse effects. Nanocochleates was prepared by ionic crosslinking method. The in-vitro release was studied at different pH conditions 7.4 and acidic pH 5.3. The formulation shows maximum entrapment efficiency of 86.22 ± 3.41% and good stability. Prolonged drug release was observed in pH 5.3 when compared to pH 7.4. Particle size was found in the range of 0.94 to 1.8 μm and the zeta potential was -7.3 ±3.3mV. Moreover, the stability studies of the prepared formulation show excellent stability. The in-vitro MTT assay was performed using the MCF-7 breast cancer cell lines. CYT- NCs were more cytotoxic than CY solution at 24hrs. These results suggest that CY-NCs can be explored for treatment of leukemia owing to their ability of providing sustained drug release, stability and improved cytotoxicity in MCF-7 cell line.